The roles of 'Ulama in Kedah:the contribution of Shaykh al-Islam Wan Sulaiman Wan Sidek (1874-1935) - Mat Zain, Farid; Zakariya, Hafiz (IIUM Press, 2017)
This book analyses the life and times of Shaykh Wan Sulaiman Wan Sidek. It utilizes the method of historical research.